PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP ATTITUDE TOWARD USING SERTA DAMPAKNYA TERHADAP BEHAVIORAL INTENTION - Ramadya, Ivan Rifqi (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
The current use of technology has made banks provide better services to their client, one of which is by launching information technology-based banking transaction service media, i.e. mobile banking. Bank Rakyat Indonesia ranked second in mobile banking users in 2020 with the percentage of 20.5 percent. However, the rate decreased to 17 percent in 2021. This is an indication that the behavioral intention of Indonesians to use the mobile banking service of Bank Rakyat Indonesia is not optimal. The sample of this explanatory research was selected using non-probability sampling method and purposive sampling technique, from which 170 users of the mobile banking service were selected as the sample. The data was analyzed in Lisrel 8.8 This study finds that perceived ease of use positively and significantly influences perceived usefulness, perceived ease of use positively and significantly influences attitude toward using, perceived usefulness positively and significantly influences attitude toward using, attitude toward using positively and significantly influences behavioral intention, perceived ease of use positively and significantly influences behavioral intention, dan perceived usefulness positively and significantly influences behavioral intention.